Analisis Etika Profesi Hakim Dalam Menegakan Keadilan Dalam Peradilan Militer - Yandi Kurniawan; Kayus Kayowuan Lewoleba (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Military Judges may face situations that can limit their freedom and independence, whether from internal or external factors. Institutionally, the legal relationship between judges and superiors can be direct, indirect, involve authority, or be within the organizational structure. Apart from that, in terms of legal substance, there are still several regulations which are considered by some members of the public to be limiting and have the potential to interfere with the independence of Military Judges. In an effort to maintain the independence of judges, judges need to adhere to legal principles, investigate legal facts at trial, and consider factors in a systematic way. The judge's decision, as a result of the Procedural Law, is expected to provide certainty, justice and benefits for all groups.